Nucleic acid-based tissue biomarkers of urologic malignancies*. (August 2014) - Dietrich, Dimo; Meller, Sebastian; Uhl, Barbara; Ralla, Bernhard; Stephan, Carsten; Jung, Klaus; Ellinger, Jörg; Kristiansen, Glen
Abstract Molecular biomarkers play an important role in the clinical management of cancer patients. Biomarkers allow estimation of the risk of developing cancer; help to diagnose a tumor, ideally at an early stage when cure is still possible; and aid in monitoring disease progression. Furthermore, they hold the potential to predict the outcome of the disease (prognostic biomarkers) and the response to therapy (predictive biomarkers). Altogether, biomarkers will help to avoid tumor-related deaths and reduce overtreatment, and will contribute to increased survival and quality of life in cancer patients due to personalized treatments. It is well established that the process of carcinogenesis is a complex interplay between genomic predisposition, acquired somatic mutations, epigenetic changes and genomic aberrations. Within this complex interplay, nucleic acids, i.e. RNA and DNA, play a fundamental role and therefore represent ideal candidates for biomarkers. They are particularly promising candidates because sequence-specific hybridization and amplification technologies allow highly accurate and sensitive assessment of these biomarker levels over a broad dynamic range. This article provides an overview of nucleic acid-based biomarkers in tissues for the management of urologic malignancies, i.e. tumors of the prostate, testis, kidney, penis, urinary bladder, renal pelvis, ureter and other urinary organs. Special emphasis is put on genomic, transcriptomic and epigenomic biomarkers (SNPs, mutations [genomic and mitochondrial], microsatellite instabilities, viral and bacterial DNA, DNA methylation and hydroxymethylation, mRNA expression, and non-coding RNAs [lncRNA, miRNA, siRNA, piRNA, snRNA, snoRNA]). Due to the multitude of published biomarker candidates, special focus is given to the general applicability of different molecular classes as biomarkers and some particularly promising nucleic acid biomarkers. Furthermore, specific challenges regarding the development and clinical implementation of nucleic acid-based biomarkers are discussed.